Echinocandins in invasive candidiasis. Issue 6 (7th May 2013) - Simon, John; Sun, Hsin‐Yun; Leong, Hoe Nam; Barez, Marie Yvette C.; Huang, Po‐Yen; Talwar, Deepak; Wang, Jen‐Hsien; Mansor, Melor; Wahjuprajitno, Bambang; Patel, Atul; Wittayachanyapong, Siriporn; Sany, B. Shoib Mohd; et al.
Summary: We summarise a recent meeting, sponsored by Pfizer Inc., where experts in Asia shared their clinical experience in managing IC. The echinocandins have demonstrated good activity against non‐ albicans infections and also azole‐resistant strains, both preclinically and in recent clinical trials. As well as proving efficacious, echinocandins have a favourable safety profile and are well tolerated, including among inpatient subpopulations, such as transplant recipients and those with renal or hepatic dysfunction. In addition the echinocandins generally have minimal drug–drug interactions, unlike the oral azoles, which have multiple effects on cytochrome P450‐mediated drug metabolism. Echinocandins are characterised by a good safety profile, few drug–drug interactions and good susceptibilities. With the increase in potentially azole‐resistant non‐ albicans infections, echinocandins may become the first‐line treatment of choice for many patients.